2011
DOI: 10.1111/j.1651-2227.2011.02166.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of television viewing between children with autism spectrum disorder and controls

Abstract: There is an earlier onset and higher frequency of television viewing in autistic children compared with children with typical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 29 publications
4
60
0
1
Order By: Relevance
“…Our findings of higher television and screen time among children with ASD compared to TD children are in agreement with a few other studies conducted in this population, although the magnitude of the difference between the groups differs among studies. A Thai study of children with ASD and TD children found that children with ASD watched more than twice as much television compared to TD children and were less likely to watch television with caregivers (Chonchaiya et al, 2011). In a US study of parents of children 2–11 years old with ASD and TD peers reported in abstract form only, May et al (2010) found that children with ASD watched 3.8 hours of television daily compared to 3.1 hours in TD peers.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of higher television and screen time among children with ASD compared to TD children are in agreement with a few other studies conducted in this population, although the magnitude of the difference between the groups differs among studies. A Thai study of children with ASD and TD children found that children with ASD watched more than twice as much television compared to TD children and were less likely to watch television with caregivers (Chonchaiya et al, 2011). In a US study of parents of children 2–11 years old with ASD and TD peers reported in abstract form only, May et al (2010) found that children with ASD watched 3.8 hours of television daily compared to 3.1 hours in TD peers.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the watching of television, studies conducted elsewhere reported similar findings to ours. For example, Chonchaiya and colleagues found that children with autism spectrum disorders began to watch television significantly earlier than controls and spent more time watching television than typically developing children [15]. Since television is nearly always watched indoors, separating out the affect of being indoors versus watching television in and of itself would have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Although children in the general population exhibit high levels of television viewing, children with ASD appear to have particularly high levels based on both nationally representative [90] and non-representative samples [91, 92]and appear to start viewing at a younger age [93]. Children with ASD are often particularly visually oriented, which may manifest as a high interest in television and computers, and have shown better responses to verbal directives delivered via video clips than by live human presentations [92].…”
Section: Risk Factors For Obesity In Children With Developmental Disamentioning
confidence: 99%